Evaluation of problematic Internet usage, characteristics of Internet usage, and other related psychiatric factors in adolescents with acne - Evrim Aktepe; Ijlal Erturan; Adem Isik (Wolters Kluwer Medknow Publications, 2020)
Background: Adolescents are psychologically more unstable and are at risk for acne and problematic Internet usage (PIU). Objectives: We aimed to evaluate PIU and characteristics of Internet usage in adolescents with acne and compared it with a control group. In addition, the relationship between psychiatric variables and problematic Internet use was examined. Methods: The study included 93 adolescents with acne and 93 healthy adolescents who were matched for age, sex, and educational level. Information forms on Internet usage characteristics, PIU Scale-Adolescent, Satisfaction with Life Scale, University of California, Los Angeles-Loneliness Scale short form, and Social Anxiety Scale for Adolescents were applied to the case and control groups. In addition, a global acne grading system and Acne Quality of Life Scale were applied to the case group. Results: PIU, duration of daily Internet usage, and membership of social sharing sites were higher in adolescents with acne than the control group. Decreased quality of life, decreased satisfaction with life levels, and increased social anxiety/loneliness levels were observed in adolescents with acne. In addition, it was determined that life satisfaction of adolescents with acne decreased at par with their quality of life; moreover, increases in the level of loneliness/social anxiety were accompanied by increases in PIU. Conclusion: The negative impact of acne on the quality of life, satisfaction with life, loneliness, and social anxiety may lead to the transition of adolescents with acne to PIU.